2021
DOI: 10.1186/s13287-021-02157-4
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium-preconditioned EPCs enhanced the ability in oligovascular repair in cerebral ischemia neonatal rats

Abstract: Background Oligovascular niche mediates interactions between cerebral endothelial cells and oligodendrocyte precursor cells (OPCs). Disruption of OPC-endothelium trophic coupling may aggravate the progress of cerebral white matter injury (WMI) because endothelial cells could not provide sufficient support under diseased conditions. Endothelial progenitor cells (EPCs) have been reported to ameliorate WMI in the adult brain by boosting oligovascular remodeling. It is necessary to clarify the role… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Co-treatment of HBMEC and OECs with OEC-CM in the current study attenuated the apoptotic effects of TNF-α, markedly increased cell viability and invariably helped maintain appropriate BBB function. Treatment of oligodendrocyte precursor cells subjected to oxygen–glucose deprivation with EPC-CM has previously been shown to inhibit apoptosis [ 62 ]. Activation of canonical NF-κB pathway that regulates expression of various genes related to cell survival, proliferation, differentiation and inflammatory responses may also be instrumental in TNF-α-evoked barrier disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Co-treatment of HBMEC and OECs with OEC-CM in the current study attenuated the apoptotic effects of TNF-α, markedly increased cell viability and invariably helped maintain appropriate BBB function. Treatment of oligodendrocyte precursor cells subjected to oxygen–glucose deprivation with EPC-CM has previously been shown to inhibit apoptosis [ 62 ]. Activation of canonical NF-κB pathway that regulates expression of various genes related to cell survival, proliferation, differentiation and inflammatory responses may also be instrumental in TNF-α-evoked barrier disruption.…”
Section: Discussionmentioning
confidence: 99%
“…EPCs were first initially discovered in 1997 by Asahara et al EPCs are defined as a cell population capable of differentiating into mature ECs and have vasculogenic potential, which contributes to vasculogenic, wound healing ( Asahara et al, 1997 ) and repair of ischemic tissue damage ( Fan et al, 2014 ). As a potential therapeutic agent, EPCs have attracted attention for a variety of diseases including cerebral ischemia ( Zhou et al, 2021 ), diabetes ( Wang K. et al, 2020 ), ALI etc. ( Asahara et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin promotes the survival and proliferation of NG2-glia through the integrin signaling pathway (Osawa et al, 2017). However, some studies have reported that fibronectin on EVs of endothelial cells mediates their internalization into NG2-glia and that EVs promotes the survival and proliferation of NG2-glia independent of the integrin signaling pathway (Osawa et al, 2017;Zhou et al, 2021).…”
Section: Interaction Of Ng2-glia With Endothelial Cellsmentioning
confidence: 99%